Influence of Nanosemiconductor Materials on Thermal Stability of Solar Cells - Aijie Ma (International Journal of Analytical Chemistry)
In order to overcome the problem of long-term stability of perovskite solar cells, the author proposes a method to study the effects of nanosemiconductor materials on the thermal stability of solar cells. In this method, n = 3 and n = 1 (C6H5(CH2)2NH3)2(CH3NH3)n-1Pbn I3n+1 two-dimensional nanoperovskite films were investigated on glass substrates and indium tin oxide (ITO) substrates, respectively, on the thermal stability. Experimental results show that the glass-based nanoperovskite PMPI3 film was partially decomposed into PbI2 after being heated at 160°C. When the temperature reaches 180°C, the film is completely decomposed into PbI2, and the perovskite PMPI3 film with ITO as the substrate is completely decomposed into PbI2 when the heating temperature reaches 140°C. The charge transfer between the perovskite film and the substrate is the physical reason for its easier thermal decomposition on the ITO substrate. Suggestions for improving the thermal stability of perovskite solar cell devices are given from the aspects of device design and fabrication process.